2014
DOI: 10.2214/ajr.13.11384
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Registration of Images Obtained Before and After Radiofrequency Ablation of Hepatocellular Carcinoma to Assess Treatment Adequacy

Abstract: Three-dimensional registration of pre- and postablation CT or MRI more accurately assesses the ablative margin than the conventional method. It can predict a proclivity for local recurrence after RFA according to margin grade. It also indicated that residuals and sites of no margin proximate to blood vessels that are more than 3 mm in diameter are high-risk locations for local recurrence after ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 20 publications
0
27
1
Order By: Relevance
“…The likelihood of local progression increases with tumor size as a result of satellite nodules (8), which is why a 5-mm minimum ablation margin is recommended by several studies (9,10). However, some of these studies (9,11,12) used a rigid registration that is not optimal for the liver because of significant deformations by respiratory movements and the ablation zone (13). Moreover, these studies assessed only two-dimensional minimal margins, failing to take into account the heterogeneous shape of the ablative volume around the tumor and that the minimal margin is not necessarily indicative of the margin sizes all around the tumor.…”
mentioning
confidence: 99%
“…The likelihood of local progression increases with tumor size as a result of satellite nodules (8), which is why a 5-mm minimum ablation margin is recommended by several studies (9,10). However, some of these studies (9,11,12) used a rigid registration that is not optimal for the liver because of significant deformations by respiratory movements and the ablation zone (13). Moreover, these studies assessed only two-dimensional minimal margins, failing to take into account the heterogeneous shape of the ablative volume around the tumor and that the minimal margin is not necessarily indicative of the margin sizes all around the tumor.…”
mentioning
confidence: 99%
“…The effectiveness of RFA treatment has conventionally been assessed by side-by-side comparison of pre-and post-RFA CT images [8][9][10][11][12][13][14]20]. However, because this side-by-side interpretation tends to be inaccurate, several new methods have been developed for more accurate treatment evaluation, such as nonenhanced MR imaging [21], superparamagnetic iron oxide-MR imaging [22,23], Gd-EOB-DTPA-MR imaging [24], and iodized oil retention [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, because this side-by-side interpretation tends to be inaccurate, several new methods have been developed for more accurate treatment evaluation, such as nonenhanced MR imaging [21], superparamagnetic iron oxide-MR imaging [22,23], Gd-EOB-DTPA-MR imaging [24], and iodized oil retention [25]. CT-CT/MR-MR fusion imaging was recently developed and is considered to be a useful imaging modality for RFA evaluation in terms of its accuracy, quantitative nature, noninvasiveness, and applicability to hypovascular lesions [8][9][10][11][12][13][14]. In the present study, we analyzed the clinical Group I: margin <0 mm (tumor extends outside the ablation zone); group II: margin 0 to <5 mm; group III: margin ≥5 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sakakibara et al [13] previously used side-by-side comparisons of preand post-RFA imaging studies in 139 HCC nodules in 84 patients, and retrospectively performed 3D registration on the imaging from the same studies. They found that histological grade at the margin and proximity to blood vessels ≥3 mm were predictors of tumor recurrence.…”
Section: Assessment Of Hcc Treatmentmentioning
confidence: 99%